A Local Transboundary Approach to the Governance of Mediterranean Coastal Borderlands. Issue 5 (3rd September 2018) - Berzi, Matteo; Ariza, Eduard
Abstract: Coastal borderlands are subjected to particular socioeconomic, political and environmental dynamics in Europe and worldwide. The presence of the international boundary in these areas poses challenges in the process of Integrated Coastal Zone Management (ICZM). The aim of this paper is to explore the existence, characteristics and the role that local cross-border cooperation plays in transboundary coastal zone management as well as the resulting potentialities of local endogenous development for improving the management and governance of the tourism sector, coastal development, fisheries and marine protected areas in the Albera Marítima (Northwestern Mediterranean). The applied methods included document review, statistical information and semi-structured interviews. The research shows that local agents are not capable of developing a stable cross-border network due to persisting lack of trust, weak joint strategic vision and high competitiveness in sectors like fishery and tourism. Based on particularly interesting initiatives occurred in Albera Marítima and other successful experiences in Mediterranean coastal borderlands, a proposal has been made to implement several measures, including a transboundary integrated coastal plan, the joint observatory of fishery resources and a scientific network platform. For the aforementioned issues, the study contributes to the ICZM literature by providing a new perspective on local transboundary cooperation.